О разрешимости в замкнутой форме нелокальной задачи для уравнения смешанного типа второго рода - Вирченко, Н.А.; Репин, О.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The paper is devoted to the solvability of a nonlocal problem for a fractional differential equation of the mixed type of the second kind.